Estimating Conveyance Efficiency and Maize Productivity of Traditional Irrigation Systems in Usa River Catchment, Tanzania - Humuri K. Haymale; Karoli N. Njau; Frederick C. Kahimba (International Journal of Agronomy)
Estimating the conveyance efficiency of traditional irrigation schemes systems is very important. It is because of understanding the volume of water lost along with the transportation facility, enhancing water usage and productivity, hence making better decisions about the utilization of water resources. The objective of the study was to determine water abstraction permit compliances and estimate conveyance efficiency and crop and water productivity of traditional irrigation systems in northern Tanzania. The task involved measurement of irrigation water flows to determine the amount of water abstraction, inflow (head) and outflow (tail) between the canals to determine the conveyance efficiency of the main, secondary, and tertiary canals of the traditional irrigation systems. Moreover, water and yield obtained at the farm level were determined. Results indicate that approximately 72% of water transported reaches the destined farm which produced maize (Zea mays L) yields of 1054.5 kg/ha, 892.4 kg/ha, and 875.156 kg/ha at downstream, midstream, and upstream which equals 0.41 kg/m3, 0.15 kg/m3, and 0.09 kg/m3, respectively, while about 28% of water is lost along the canals through evaporation, seepage, and deep percolation and overtopping. Consequently, water measured at furrow intakes in total was 3,500 L/s, equal to 23% more than the permitted amount of 2856.14 L/s at Usa River Catchment. Interventions to minimize water losses starting at the furrow’s intakes are urgently required in the current trend of the increasing demand for water resources for food production and schemes performance. Subsequently, more effective conveyance technologies and water management strategies other than canal lining are required.